Spatial design : breaking the 2D paradigm - Wu, Dominique, ....-; Kress, Jeremy (red.), ....-; Pham, Lily (ill.), ....- (Milton Keynes : Ingram Content Group UK Ltd., 2024)
This book serves as a comprehensive guide for the shift from traditional 2D interfaces to the immersive realm of spatial design, capturing the collective wisdom of 38 visionaires in the field. It lays down essential principles for designing engaging 3D spaces that seamlessly integrate virtual and physical worlds, making it an indispensable manual for designers venturing into spatial computing.
Keywords: User interfaces